What Is Specific and What Is Shared Between Numbers and Words? - Lopes-Silva, Júlia B.; Moura, Ricardo; Júlio-Costa, Annelise; Wood, Guilherme; Salles, Jerusa F.; Haase, Vitor G. (Frontiers in Psychology, 2016)
Reading and spelling performance have a significant correlation with number transcoding, which is the ability to establish a relationship between the verbal and Arabic representations of numbers, when a conversion of numerical symbols from one notation to the other is necessary. The aim of the present study is to reveal shared and specific mechanisms involved in reading and writing words and Arabic numerals in Brazilian school-aged children. One hundred and seventy two children from 2nd to 4th grades were evaluated. All of them had normal intelligence. We conducted a series of hierarchical regression models using scores on word spelling and reading single words and Arabic numerals, as dependent variables. As predictor variables we investigated intelligence, the phonological and visuospatial components of working memory and phonemic awareness. All of the writing and reading tasks (single word spelling and reading as well as number reading and number writing) were significantly correlated to each other. In the regressions models, phonological working memory was specifically associated to word reading. Phonemic awareness was the only cognitive variables that systematically predicted all of the school skills investigated, both numerical and word tasks. This suggests that phonemic awareness is a modular cognitive ability shared by several school tasks and might be an important factor associated to the comorbidity between dyslexia and dyscalculia.